Effect of concentration on the tribological behavior of cyclic heated formulated organic carbon nanotubes in base lubricant under boundary conditions - Opia, Anthony Chukwunonso (Japanese Society of Tribologists, 2021)
The tribological enhancement of base lubricant under different concentration of formulated Eichhornia Crassipes carbon nanotubes (EC-CNTs) was conducted in this research. Cyclic heating approach was adopted in the formulation of EC-CNT and scientifically characterized. The characterization results confirmed the sample EC-CNTs. The effect of EC-CNT in base rapeseed oil terms of concentration, coefficient of friction (COF) and surface roughness (Ra), load carrying capacity, lubrication film stability and film mechanism were evaluated using high frequency reciprocating rig machine. The results showed that inclusion of EC-CNTs into base rapeseed oil, enhanced the tribological properties. The resultant values of COF were 0.064, 0.051 and 0.087 for rapeseed blended 1 mass%, 2.5 mass%, 4 mass% EC-CNT respectively. This is 38.5% COF reduction from 2.5 mass% EC-CNT against base oil. Under wear scar diameter, 2.5 mass% showed 47.9% reduction compared to base oil. The Ra was reduced with addition of nanoparticles, especially with 2.5 mass%. The tribological enhancement by EC-CNT is attributed from tribo-chemical reaction between the particles and the interfaces leading to formation of active protective tribo-film. The mechanism exhibited by the nanoparticles were healing and rolling from which the tribo-enhancement were achieved.